Analysis of User Satisfaction in Mobile Banking Applications: A Technology Acceptance Model Approach at BRI Manokwari - Yammes Jonas Batkunde (Economics and Digital Business Review, 2025)
This study aims to determine the perceived ease of use and perceived usefulness on customer satisfaction of mobile banking application users at BRI Manokwari, partially and simultaneously. The study uses a quantitative approach; the research sample is 100 respondents (Lemeshow approach), the data analysis technique uses multiple linear regression, while the data collection technique uses Google Form, and the data processing uses the SPSS IMB 26 application. The results of the study show that ease of use has a positive and significant effect on customer satisfaction. Perceived usefulness does not have a positive and significant effect on customer satisfaction. Ease of use and perceived usefulness simultaneously have a significant effect on customer satisfaction. This shows that the easier banking services are to use and the greater the benefits perceived by customers, the level of customer satisfaction with BRI Bank services will also increase.